Врахування кінцевої швидкості поширення тепла при лазерному розігріві поверхні твердого тіла - Porodko, L. V.; Lerman, L. B.; Semchuk, O. Yu. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
The thermal effects are considered caused by the laser irradiation of external of solid surface with taking limited speed of heat expansion into account. Numeral calculations are presented on temperature distribution through the solid surface for different action band widths of laser radiation. An analytical expression has been got for the error evaluated due to taking into account the limited speed of heat expansion. The increase in the period of interference picture has been shown to result in localization of maximum values of temperature within the action zone of laser beams. This effect increases provided the limited speed of heat expansion is taken into account.